2020
DOI: 10.33776/erebea.v10i0.4961
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and Individual Predictors of Bullying and Victimization in Slovenia: Positive Youth Development Perspective

Abstract: Bullying and victimization pose a serious risk for youth optimal development due to numerous negative short-and longterm consequences. One of the models with a focus on adolescents that can serve as a theoretical framework in designing prevention and intervention programmes targeting bullying and victimization is Positive Youth Development Perspective. The Positive Youth Development perspective assumes that with the positive interplay between developmental assets (internal and external youth resources) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…While exploring young immigrants' positive youth development, the questions of who adapts successfully and what are the preconditions for success remain unanswered (Motti-Stefanidi, 2017). One model which effectively promotes positive aspects of adolescents' development and is used by several researchers to explore this area is the 5Cs of the Positive Youth Development (PYD) model (Fuligni, 2004;Kozina & Pivec, 2020;Lerner et al, 2012Lerner et al, , 2015Wiium & Dimitrova, 2019). Although a number of models of positive youth development exist, the 5Cs model is the most empirically supported and most commonly used as the framework for programmes supporting positive youth development (Heck & Subramaniam, 2009).…”
Section: Immigrant Background As a Framework For Positive Youth Developmentmentioning
confidence: 99%
“…While exploring young immigrants' positive youth development, the questions of who adapts successfully and what are the preconditions for success remain unanswered (Motti-Stefanidi, 2017). One model which effectively promotes positive aspects of adolescents' development and is used by several researchers to explore this area is the 5Cs of the Positive Youth Development (PYD) model (Fuligni, 2004;Kozina & Pivec, 2020;Lerner et al, 2012Lerner et al, , 2015Wiium & Dimitrova, 2019). Although a number of models of positive youth development exist, the 5Cs model is the most empirically supported and most commonly used as the framework for programmes supporting positive youth development (Heck & Subramaniam, 2009).…”
Section: Immigrant Background As a Framework For Positive Youth Developmentmentioning
confidence: 99%
“…In studying Positive Youth Development (PYD), the 5Cs model (competence, confidence, connection, character, caring) is widely used (Kozina & Pivec, 2020;Lerner et al, 2012Lerner et al, , 2015Wiium & Dimitrova, 2019). Chosen for its empirical support and flexibility (Heck & Subramaniam, 2009), PYD focuses on identifying and supporting strengths rather than deficits, enhancing positive development and resilience (Masten, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, Filbert and Flynn (2010) presented how young people's possession of more developmental assets was associated with more resilience, assessed by more prosocial behaviour, greater self-esteem, better educational performance, and fewer behavioural difficulties in a sample of First Nations young people in care. Kozina and Pivec (2020) studied cross-sectional relationships between developmental assets and bullying among students in Slovenia. They found that less empowerment predicted social bullying, while less constructive use of time was related to verbal victimisation.…”
mentioning
confidence: 99%